DINAMIKA POLITIK HUKUM PERBANKAN SYARIAH PASCA UNDANG-UNDANG NO. 21 TAHUN 2008 - Abdul Fatakh; Rabith Madah Khulaili Harsya (UIN Siber Syekh Nurjati Cirebon, 2023)
Syari’ah economic practice actually has been widely recognized by Indonesian Moslem. However, a new positive form of this practice only begins after reformation period by the establishment of Undang-undang Nomor 10 Tahun 1998 tentang Perubahan Undang-undang Nomor 7 Tahun 1992, and Undang-undang Nomor 21 Tahun 2008 tentang Perbankan Syari’ah. Act on Syari’ah Banking has been delivered as the governmental appreciation and accommodation to public norms (living law). Moreover, economic practice access with syari’ah principle becomes so facilitated, and thus, any banking conventional activities appear being easily conducted in benefiting banks in general while preserving the costing pattern and other issues based on syari’ah principle.This type of research is library research (library research), in the sense that all data sources come from written materials in the form of books, documents, magazines and texts that are related to the topic of discussion through a review of various literature related to research which includes primary, secondary data. , dantertier. The data collected, read.The political dynamics of sharia economic law in legislation as a form of juridical implementation of sharia economics can be seen from Law of the Republic of Indonesia Number 7 of 1992 concerning Banking, where sharia banks are understood as profit-sharing banks. The rest of the sharia banks must comply with conventional-based general banking regulations. Key Words: Regulation, Syaria’ah Banking, Competence